A bottom‐up modeling of metabolism of the residential building system in China toward 2050. (27th January 2023) - Zhang, Ling; Lu, Qingqing; Yuan, Zengwei; Jiang, Songyan; Wu, Huijun
Abstract: This study predicted the metabolic process of the residential building system in China toward 2050 by addressing the detailed provincial patterns and urban–rural disparity and the characterizing metabolisms of building materials in detail. The results show that after a rapid growth during 1980–1990, the in‐use stocks of residential buildings in China are expected to slow down in around 2030, reaching 75 billion m 2 in 2050. Urban regions will account for 80% of total stocks, and provinces in the eastern and southern coastal areas will have the largest share. As demolition lags construction, the end‐of‐life residential buildings will continue to grow steadily with huge urban–rural and provincial differences, reaching 1.4 billion m 2 by 2050. Regarding the metabolism of building materials, the inflow of most materials will decrease after 2030, while the outflow will increase steadily toward inflow. Based on the recycling outlook of construction and demolition waste and the corresponding environmental benefit, it is indicated that under the Chinese government's ambitious planning and vigorous promotion, prior to the middle of the century, the building system has the potential to transition to a sustainable future that meets residents' housing needs with a remarkable decreasing input of raw materials thereby notably decreasing pressures on the environment, which will significantly benefit the goal of carbon neutrality in China.